الصعوبات التي تواجه أساتذة التربية البدنية والرياضية أثناء سير الحصة في مرحلة التعليم المتوسط - قريشي يونس. بلواعر جهيد (My University, 2025)
abstract : Title: The Difficulties and Obstacles Faced by Physical Education Teachers in Their Professional Life (Middle School Level) This study aims to identify the difficulties and obstacles that hinder middle school physical education teachers from achieving their goals and fulfilling their duties. The researcher used the descriptive method to test the study’s hypotheses, which included the following: physical education teachers experience professional pressures from the school administration; the working conditions during physical education classes are inadequate; teachers are generally satisfied with their profession; and there are statistically significant differences in professional difficulties based on years of experience. The research sample consisted of 34 middle school physical education teachers from the Skikda province. The researcher used statistical methods such as percentages, arithmetic means, and standard deviations. The findings revealed that physical education teachers face various challenges and obstacles in their profession. Most teachers do not encounter issues with school administration. However, overcrowded classes hinder the effective implementation of physical education sessions. Moreover, sports facilities and equipment in most schools are insufficient, unequipped, and inappropriate. Despite these issues, most teachers are passionate about their profession and are satisfied with their academic and social status. The study also concluded that the challenges faced by physical education teachers are not significantly related to their level of professional experience. الملخص: الصعوبات والعراقيل التي تواجه أستاذ التربية البدنية والرياضية ف حياته المهنية (الطور المتوسط): تهدف هذه الدراسة إلى التوصل لمعرفة الصعوبات والعراقيل التي تقف في وجه أستاذ التربية البدنة والرياضية في الطور المتوسط، والتي تحول دون وصوله إلى تحقيق أهدافه وتأدية مهامه، وقد استخدم الباحث المنهج الوصفي لتحقيق فرضيات الدراسة التي كانت:- أستاذ التربة البدنية والرياضية يعاني من ضغوطات مهنية من طرف الادارة، وظروف العمل أثناء إنجاز حصة التربية البدنية والرياضية غير ملائمة، وأن أساتذة التربية البدنية والرياضية راضون عن مهنتهم وأيضا هناك فروق ذات دلالة إحصائية في الصعوبات المهنية تعزى لمتغير الخبرة المهنية، تمثلت عينة البحث في أساتذة التربية البدنية والرياضة في الطور المتوسط لولاية سكيكدة والبالغ عددهم 34 أستاذ، واستخدم الباحث الأساليب الإحصائية، النسب المئوية، المتوسطات الحسابية والانحرافات المعيارية، واستخلص من الدراسة: وجود صعوبات وعراقيل تعترض أساتذة التربية البدنية والرياضية.- أغلب الأساتذة لا يواجهون مشاكل من طرف الإدارة. – كثرة التلاميذ في القسم الواحد لا يساعد على إجراء حصة التربية البدنية والرياضية. – المنشآت والامكانات الرياضية في أغلب المؤسسات غير كافية وغير مجهزة وغير مناسبة.- أغلب أساتذة التربية البدنية والرياضية لديهم ميول لهذه المهنة وهم راضين عن مكانتهم العلمية والاجتماعية. – العراقيل التي تواجه أساتذة التربية البدنية والرياضية ليس لها علاقة بمستويات الخبرة. résumé : Titre : Difficultés et obstacles rencontrés par les enseignants d’éducation physique (collège) Cette étude vise à identifier les difficultés et les obstacles qui empêchent les enseignants d’éducation physique (EPS) au collège d’atteindre leurs objectifs et de s’acquitter de leurs fonctions. Le chercheur a utilisé la méthode descriptive pour tester les hypothèses suivantes : les enseignants d’EPS subissent des pressions professionnelles de la part de l’administration ; les conditions de travail pendant les cours d’EPS sont inadéquates ; les enseignants sont généralement satisfaits de leur profession ; et il existe des différences statistiquement significatives dans les difficultés professionnelles selon le nombre d’années d’expérience. L’échantillon de recherche était composé de 34 enseignants d’EPS au collège de la province de Skikda. Le chercheur a utilisé des méthodes statistiques telles que les pourcentages, les moyennes arithmétiques et les écarts types. Les résultats ont révélé que les enseignants d’EPS sont confrontés à divers défis et obstacles dans leur profession. La plupart des enseignants ne rencontrent pas de problèmes avec l’administration scolaire. Cependant, la surpopulation des classes entrave la mise en œuvre efficace des séances d’EPS. De plus, les installations et équipements sportifs dans la plupart des écoles sont insuffisants, mal équipés et inadaptés. Malgré ces difficultés, la plupart des enseignants sont passionnés par leur profession et satisfaits de leur statut académique et social. L'étude conclut également que les difficultés rencontrées par les enseignants d'éducation physique ne sont pas significativement liées à leur niveau d'expérience professionnelle.
دراسةميدانيةلبعض متوسطاتولاية سكيكدة
Keywords: Obstacles; Physical Education Teachers; Professional Life; الصعوبات; أساتذة التربية البدنية والرياضية; حصة التربية البدنية والرياضية; Enseignants d'éducation physique; Vie professionnelle